Analysis of the Environmental Impact of Sugarcane Cultivation on Ecotoxicity, Land Use Competition and Depletion of abiotic resources with Life Cycle Assessment (Case Study: Madukismo Sugar Factory, Yogyakarta, Indonesia) - Lolo, Elvis Umbu; Widianto, Widianto; Ngalung, Alfred Dedu (Journal of Environmental and Science Education, 2023)
Madukismo Sugar Factory used Ametryn and 2,4 d.amine as herbicides, and Urea, NPK, and ZA fertilizers, in its sugarcane cultivation process. This study performed life cycle assessment to see its environmental impact and proposed sustainable improvement efforts. The factory's sugarcane cultivation was found to account for 1041.085927 kg 1,4-DCB- Eq of Freshwater aquatic ecotoxicity-FAETP 100a, 6.702603784 kg 1,4-DCB-Eq of Terrestrial ecotoxicity-TAETP 100a, 689.8995889 m2a of Land use– competition, and 171.1111422 kg antimony-Eq of Depleted abiotic resources. The improvement could be made by applying biological pest controls, such as trichogamma chilonis, Cotesia flavipes, Sturmiopsis inferens, Tetrastichus scoenobii and elasmus zehteneri. The NPK, ZA, and urea fertilizers should also be used according to the standard operating procedure set by the Ministry of Agriculture, particularly regarding its amount and duration (at least twice a year). Manure could also be used to decrease dependency on synthetic fertilizers. Filter cake should also be used as organic fertilizer in sugarcane cultivation.